The selective ERβ agonist AC 186 reduces polyinosinic:polycytidylic acid (poly I:C)-induced inflammatory responses in BEAS-2B lung epithelial cells - Olajide, Olumayokun A.; Ogiogio, Hope A. (Frontiers in Pharmacology, 2025)
BackgroundAcute respiratory distress syndrome (ARDS) is characterised by inflammation with the accompanying release of pro-inflammatory cytokines. AC186 is an oestrogen receptor agonist, which has shown anti-inflammatory activity. This study investigated effects of AC186 on poly I:C-induced inflammation in human bronchial epithelial (BEAS-2B) cells.MethodsSupernatants from poly I:C-stimulated BEAS-2B cells treated with AC186 (1.25, 2.5 and 5 µM) were analysed for levels of tumour necrosis factor-alpha (TNFα), interleukins-6 (IL-6), -1β (IL-1β) and −8 (IL-8), using ELISA. Protein expression of phospho-p65 NF-κB was evaluated using Lumit® Immunoassay, while nuclear localisation, DNA binding and transcriptional activity of NF-κB were evaluated using immunofluorescence, transcription factor ELISA and reporter gene assays, respectively. In cell ELISAS were used to determine effects on NLRP3 and caspase-1 proteins while Caspase-Glo® 1 inflammasome assay was used to determine whether AC186 influenced caspase-1 activity. Experiments were conducted to evaluate effects on ATP production and caspase 3/7 activity.ResultsAC186 produced significant (p < 0.05) reduction in elevated levels of TNFα, IL-6, IL-1β and IL-8 in BEAS-2B cells, in comparison with poly I:C stimulation alone. Increased phosphorylation of p65 was significantly (p < 0.01) reduced in the presence of AC186 (2.5 and 5 µM), while nuclear localisation of p65, as well as DNA binding and transactivation were blocked with 2.5 and 5 µM of the compound. AC186 (2.5 and 5 µM) reduced protein levels of both NLRP3 inflammasome and caspase-1, as well as caspase-1 activity. Co-administration of ICI 182780 (10 nM) with AC186 (5 μM) prior to stimulation with poly I:C resulted in higher levels of TNFα and IL-6 secretion, compared to AC186 pre-treatment alone. Following incubation of AC186 (2.5 and 5 μM) with poly I:C-stimulated BEAS-2B cells for 72 h, there was significant improvement in viability as well as reduction in caspase 3/7 activity, in comparison with poly I:C alone.ConclusionThese results suggest that AC-186 produced anti-inflammatory activity in poly I:C-stimulated BEAS-2 cells, through mechanisms involving inhibition of NF-κB and NLRP3/caspase-1/IL-1β activation. AC186 also protected BEAS-2B cells against poly I:C-mediated apoptosis and death suggesting that this compound have potentials in reducing inflammatory events associated with ARDS caused by viral infections.